Paradoks kredensi apostolik: Penderitaan sebagai retorika legitimasi dalam periautologi Paulus menurut 2 Korintus 11:23-29 - Simanullang, Tambok Tua (KURIOS, 2025)
This article examines the paradox of apostolic credentials in Paul's periautology (self-commendation) in 2 Corinthians 11:23-29 through rhetorical-critical analysis. Against the backdrop of Greco-Roman conventions of self-praise, Paul's catalogue of hardships functions not merely as emotional rhetoric (pathos) but as a deliberate inversion of periautological norms to legitimize his apostleship. By cataloging suffering rather than achievements, Paul subverts the social expectations of his Corinthian opponents and establishes a theology of the cross as the definitive criterion for apostolic authority. This study argues that the paradox of Pauline credentials, where weakness becomes the very basis of legitimacy, reflects a profound Christological conformity in which the apostle's suffering participates in and makes visible the cruciform pattern of Christ's own self-emptying. The implications extend beyond individual apostleship to ecclesiological praxis, redefining power, authority, and authentic ministry within the Christian community.   Abstrak Artikel ini mengkaji paradoks kredensi apostolik dalam periautologi (pujian-diri). Paulus di 2 Korintus 11:23-29 melalui analisis retoris-kritis. Dengan latar belakang konvensi pujian-diri dalam tradisi Greco-Romawi, katalog penderitaan Paulus berfungsi bukan sekadar sebagai retorika emosional (pathos), melainkan sebagai inversi deliberatif terhadap norma periautologis guna melegitimasi kerasulannya. Dengan mengkatalogkan penderitaan alih-alih pencapaian, Paulus mensubversi ekspektasi sosial para lawannya di Korintus dan menetapkan theologia crucis sebagai kriteria definitif otoritas apostolik. Studi ini berargumen bahwa paradoks kredensi Pauline, di mana kelemahan menjadi basis legitimasi, merefleksikan konformitas Kristologis yang mendalam, di mana penderitaan rasul berpartisipasi dalam dan memvisibilisasikan pola kenosis Kristus. Implikasinya melampaui kerasulan individual menuju praksis eklesiologis, mendefinisikan ulang kuasa, otoritas, dan pelayanan autentik dalam komunitas Kristen.